The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1021/bi9620621
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Pores Induced by Magainin

Abstract: Magainin, found in the skin of Xenopus laevis, belongs to a broad class of antimicrobial peptides which kill bacteria by permeabilizing the cytoplasmic membrane but do not lyse eukaryotic cells. The 23-residue peptide has been shown to form an amphiphilic helix when associated with membranes. However, its molecular mechanism of action has been controversial. Oriented circular dichroism has detected helical magainin oriented perpendicular to the plane of the membrane at high peptide concentrations, but Raman, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
766
5
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 751 publications
(823 citation statements)
references
References 25 publications
42
766
5
6
Order By: Relevance
“…Since the helical conformation remains unchanged over a wide range of conditions and is stabilized by aggregation, the same helical structure is expected to remain in the solid state, and this is consistent with the 13 C CPMAS experiments (Figure 2). The extent of the helical region has been predicted to range from residues 11-32 based on the percent of helical residues indicated by CD spectra and analysis of the peptide sequence, and the 13 C isotropic chemical shifts of 13 15 N spectra show that the peptide helix is aligned on the surface of the bilayer in a variety of lipid environments, as was predicted for such an amphipathic R-helix (Figures 5-7). The 15 N spectra of LL-37 in MLVs indicate that LL-37 does not rotate rapidly about the membrane normal as has been shown to occur for another surface-oriented antimicrobial peptide, ovispirin (51).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Since the helical conformation remains unchanged over a wide range of conditions and is stabilized by aggregation, the same helical structure is expected to remain in the solid state, and this is consistent with the 13 C CPMAS experiments (Figure 2). The extent of the helical region has been predicted to range from residues 11-32 based on the percent of helical residues indicated by CD spectra and analysis of the peptide sequence, and the 13 C isotropic chemical shifts of 13 15 N spectra show that the peptide helix is aligned on the surface of the bilayer in a variety of lipid environments, as was predicted for such an amphipathic R-helix (Figures 5-7). The 15 N spectra of LL-37 in MLVs indicate that LL-37 does not rotate rapidly about the membrane normal as has been shown to occur for another surface-oriented antimicrobial peptide, ovispirin (51).…”
Section: Discussionmentioning
confidence: 91%
“…The two 13 C labels are placed near either end of the helical region and used to confirm the extent of the helix. To enable easy resolution and assignment in the doubly 13 C-labeled peptide, one 13 C R and one 13 CdO label were used. Alanine was substituted for isoleucine at residue 13 due to the limited availability of 13 C R -labeled Fmoc amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Biophysical studies have demonstrated that there are some general nonreceptor-mediated mechanisms responsible for peptide antimicrobial activity, which appear to involve permeabilization of phospholipid bilayer membranes via ''barrel-stave,'' ''toroidal pore,'' or ''carpet detergent-like'' arrangements. 3,8,11,15 Since the majority of antimicrobial peptides are positively charged at physiological pH, while outer leaflets of mammalian and bacterial plasma membranes are totally neutral and anionic, respectively, the mechanisms of their antimicrobial and hemolytic activities might differ in detail.…”
Section: Introductionmentioning
confidence: 99%